Impact of NTFP Harvesting in Forest Conservation - Dangi, Resham Bdr (The Initiation, 2010)
Regardless of size, Nepal is famous for floral and faunal diversity in the world. Out of 15,000 identified plant species in this country, more than 2000 plants have medicinal properties and more than 100 plant species are in commercial trade. There is growing concern in governmental and non-governmental organization to promote NTFP for improvements of rural livelihoods and forest conservation. However, field evidences do not demonstrate its meaningful contribution in forest conservation objective. This paper attempts to appraise the bottleneck issue in maintaining Maximum sustained yield (MSY) of viable NTFPs. The analysis is more focused on production characteristics rather than demand and institutional characteristics of NTFPs. Finally, the paper concludes by recommending few potential options for improvement. The suggested intervention includes preparation of new inventory guideline; improve forestry governance, training and extension for collectors, capacity building for forestry professional, and support for strengthening market infrastructure. Key Words: Non-timber forest products (NTFP), Market demand, Harvestable quota, Maximum sustained yield (MSY), Ecological impact and forest governance DOI: 10.3126/init.v2i1.2539 The Initiation Vol.2(1) 2008 pp165-171